The Immortal Republic: The Myth of Venice during the Italian Wars (1494- 1530) - Finlay, Robert (The sixteenth century journal, 1999)
Central events of the Italian Wars (1494-1530) cannot be understood without taking into consideration the widespread perception of the immortality of the Venetian Republic. The well-known myth of Venice-the notion that the Venetian Republic embodied an ideal amalgam of freedom, justice, and stability-was paralleled by a countermyth which emphasized the imperialism and treachery of the state. These positive and negative perceptions of Venice were not sharply distinguished, however, for contemporaries in the sixteenth century saw them as delineating common aspects of Venetian reality. In particular, the premise that the republic was immortal, as seen in its immemorial origins and collective deliberations, represents the most important convergence of the myth and countermytth. Both allies and enemies of Venice took the supposed immortality of its republican structure into account when making political decisions between 1494 and 1530.